(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study was carried out to investigate the effects of Tamarind tree leaves with dry and fermentation using beneficial bacteria on growth performance, carcass characteristics, meat oxidative stability and economics of broiler rearing. A total of 90 day-old Ross-308 unsexed broiler chicks were assigned to three dietary treatments consisting of three replications having 10 birds in each for 4 weeks in a completely randomized design. Dietary treatments were, T0 = Control (basal diet), T1 (basal diet + 0.4% dried Tamarind tree leaves on DM basis) and T2 (basal diet + 0.4% fermented Tamarind leaves on DM basis). According to the results, overall average daily gain (ADG) were increased and feed conversion ratio (FCR) improved in both T1 and T2 groups compared to the control group (P<0.05). A significant increased HDL level and decreased LDL, total cholesterol and triglyceride level in all treatment groups relative to control (P<0.05). Crude protein (CP) and ether extract (EE) content of breast meat was higher (P<0.05) in T2 group than control and T1 groups. Relative breast meat and heart weight was found higher while decreased abdominal fat weight (P<0.05) in treatment groups compared to the control group. In addition, thiobarbituric acid reactive substances (TBARS) values of breast meat were reduced significantly (P<0.05) in T1 group compared to the control treatment. A significant reduction of total cost and increment of net return and benefit cost ratio (BCR) found in treatment groups particularly in T2 group compared to the control (P<0.01). Finally, dietary supplementation of Tamarind tree leaves with dry and fermented leaves improved growth performance, CP, EE, blood HDL cholesterol level and net return, while reduced blood total cholesterol, LDL cholesterol, triglyceride and meat TBARS value. Thus, it can be suggested from this study that Tamarind tree leaves can be supplemented as an effective feed additive for broilers. J Bangladesh Agril Univ 18(3): 643–650, 2020 https://doi.org/10.5455/JBAU.95075